2022
DOI: 10.3390/foods11172547
|View full text |Cite
|
Sign up to set email alerts
|

Poverty, Household Structure and Consumption of Foods Away from Home in Peru in 2019: A Cross-Sectional Study

Abstract: The aim of this study was to evaluate the probability of buying food away from home according to the type of household using the logit model, as well as the sociodemographic characteristics of the heads of household, and how much income expenditure represents. A cross-sectional study was carried out using the National Household Survey (ENAHO) 2019 database. After joining the database, the household type variables were created. To calculate the probability with the “logit” model of purchase, the variables—famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 58 publications
1
9
0
Order By: Relevance
“…There are some previous studies on circular economy and foods, but they have focused on different aspects such as the supply chain [82,83], digitalization in the food supply chain [84,85], food waste [86], and artificial intelligence in the food supply chain [87]. Moreover, systematic reviews have been published [88,89] that reported that the journals Sustainability and the Journal of Cleaner Production published the highest numbers of research papers that originated primarily in Europe.…”
Section: Introductionmentioning
confidence: 99%
“…There are some previous studies on circular economy and foods, but they have focused on different aspects such as the supply chain [82,83], digitalization in the food supply chain [84,85], food waste [86], and artificial intelligence in the food supply chain [87]. Moreover, systematic reviews have been published [88,89] that reported that the journals Sustainability and the Journal of Cleaner Production published the highest numbers of research papers that originated primarily in Europe.…”
Section: Introductionmentioning
confidence: 99%
“…Underlying data Older adults and children (Food consumed outside the home) https://doi.org/10.6084/m9.figshare.23935221.v1. 80 This project contains the following underlying data:…”
Section: Data Availabilitymentioning
confidence: 99%
“…The global distress concerning these detrimental environmental shifts has been reflected through studies exploring people's knowledge and attitudes concerning environmental consciousness, the value of environmental preservation, and the purchase of environmentally sustainable products [5][6][7]. Consumers are steadily becoming much more environmentally conscious after realizing the seriousness of environmental problems and the need to diminish the impact of human behavior and consumption on the ecosystem [8].…”
Section: Introductionmentioning
confidence: 99%